PENANGANAN MASALAH KENAKALAN REMAJA BERBASIS MASYARAKAT DI DESA CISAMBENG KABUPATEN MAJALENGKA: PERSPEKTIF PEKERJA SOSIAL - Muhammad Ilham Fahmi; Brelyantika Indra Jesa (Politeknik Kesejahteraan Sosial Bandung, 2021)
Handling a juvenile delinquency problem has become a discussion form various disciplines, one of disciplines is social work which provides a different perspective form other. Juvenile delincquency in Cisambeng is described as a problem that has strong relationship with the social environment, so in its resolution social workers bring a strength perspective, a sociopsychological perspective, and a social system perspective that is unique in its practice. This study aims to provide an overview of the solving of juvenile delinquency problems by social worker together with the community itself and how the social worker’s perspective describes the phenomenon and offers a problem-solving solution. The approach that used to describe the empowerment process and results is qualitative approach with descriptive methods. The results that presented in this study are a narrative description of how social workers carry out the empowerment process and the results. Furthermore, it describes how the strength, sociopsychological, and social system perspective sees a problem and practice-based solution that has been done by social workers in handling juvenile delinquency problem in Cisambeng.